2023
DOI: 10.1007/s00408-023-00639-1
|View full text |Cite
|
Sign up to set email alerts
|

ETS1 Ameliorates Hyperoxia-Induced Bronchopulmonary Dysplasia in Mice by Activating Nrf2/HO-1 Mediated Ferroptosis

Min Yang,
Yanping Chen,
Xueshan Huang
et al.

Abstract: Purpose Bronchopulmonary dysplasia (BPD) is associated with hyperoxia-induced oxidative stress-associated ferroptosis. This study examined the effect of E26 oncogene homolog 1 (ETS1) on oxidative stress-associated ferroptosis in BPD. Methods Hyperoxia-induced A549 cells and neonatal mice were used to establish BPD models. The effects of ETS1 on hyperoxia-induced ferroptosis-like changes in A549 cells were investigated by overexpression of ETS1 plasmid tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These genes may also play integral roles in various signaling pathways, such as the cancer pathway and MAPK signaling pathway. Notably, quercetin has previously demonstrated its ability to inhibit ferroptosis in various diseases (Wang et al, 2021), and recent research has also linked ferroptosis to BPD (Chou & Chen, 2022;Yang et al, 2023). Consequently, we identified PTGS2, NRF2, and HSPB1 as key genes based on the common targets and ferroptosis marker genes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These genes may also play integral roles in various signaling pathways, such as the cancer pathway and MAPK signaling pathway. Notably, quercetin has previously demonstrated its ability to inhibit ferroptosis in various diseases (Wang et al, 2021), and recent research has also linked ferroptosis to BPD (Chou & Chen, 2022;Yang et al, 2023). Consequently, we identified PTGS2, NRF2, and HSPB1 as key genes based on the common targets and ferroptosis marker genes.…”
Section: Discussionmentioning
confidence: 96%
“…Ferroptosis, as a relatively novel form of cell death, has only been preliminarily explored in the context of BPD (Deng et al, 2023;Ma et al, 2023;Yang et al, 2023), and its molecular mechanism remains unclear. Prior studies have demonstrated that quercetin can ameliorate various diseases by inhibiting ferroptosis (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%